(untitled) (Research, Society and Development, 2022)
This study investigated how Brazilian dentists are performing their clinical activities during the pandemic in different dentistry specialties and whether changes in biosafety protocols and the use of personal protective equipment (PPE) made will continue in the post-pandemic period. For that, a cross-sectional online questionnaire-based survey was presented to the volunteers. A total of 423 dentists (298 females) responded to the survey. Their age ranged from 22-73 (38.07 ± 10.58) years and years of dental practice ranged from 1-45 (14.68 ± 10.56). Most of the responders (66.43%) worked in private clinic. Since the beginning of the outbreak, 53.9% limited its activities only to urgent and emergency care; 75% starting limit its activities between March 18th and April 1st; and 25.88% limited for more than 15 weeks. Most of dentists are aware about the setting of dental office and are taking actions to prevent the transmission of the COVID-19 virus. The majority are all personal protective equipment. After the pandemic period, volunteers stated that will continue with the use of personal protective equipment, exception only to the use of the respirator. There was continuity of dental care, following the recommendations for safe care. There was a tendency for changes in relation to PPE to last after the end of the pandemic.